Protective effect of luteinizing hormone on frozen-thawed ovarian follicles and granulosa cells - Chen, Jie; Yu, Boyang; Zhang, Shengbo; Wang, Zhikang; Dai, Yanfeng (PLOS ONE, 2025)
Ovarian tissue cryopreservation addresses critical challenges in fertility preservation for prepubertal female cancer patients, such as the lack of viable eggs and hormonal deficiencies. However, mitigating follicle and granulosa cell damage during freeze-thaw cycles remains an urgent issue. Luteinizing hormone (LH), upon binding to luteinizing hormone receptors (LHR) on granulosa cells, enhances estrogen synthesis and secretion, contributing to the growth of granulosa cells and follicles. This study examined mouse ovarian follicles and granulosa cells to identify optimal LH treatments using morphological assessments and LIVE/DEAD assays. The study found significant increases in the expression of Leucine-rich G-protein-coupled receptor 5 (Lgr5) and Forkhead box L2 (Foxl2) in mural and cumulus granulosa cells under LH influence, alongside marked reductions in active caspase-3 expression. Double immunofluorescence of Ki67 with Foxl2 and Lgr5 revealed ongoing proliferative activity in granulosa cells post freeze-thaw. In addition, LH treatment significantly boosted the expression of transforming growth factor (TGF-β) and its superfamily members in both granulosa cells and oocytes. These findings suggest that LH addition during cryopreservation can diminish damage to follicles and granulosa cells, offering new strategies to enhance the efficacy of mammalian ovarian cryopreservation.